Function as constitutive feature of movements in sport - Wiemeyer, J. (International Journal of Computer Science in Sport, 2002)
Movements in sport can be considered a comparably complex aggregate of elements that constitute a specific structure. Function can serve as a constitutive feature in order to determine these elements of movements and their relations. Function may also serve as a criterion to determine freedom and constraints of movements.